2017
DOI: 10.1111/jvim.14800
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Multivariate Predictive Model to Estimate Ionized Calcium Concentration from Serum Biochemical Profile Results in Dogs

Abstract: BackgroundIonized calcium concentration is the gold standard to assess calcium status in dogs, but measurement is not always available.Objectives(1) To predict ionized calcium concentration from biochemical results and compare the diagnostic performance of predicted ionized calcium concentration (piCa) to those of total calcium concentration (tCa) and 2 corrected tCa formulas; and (2) to study the relationship between biochemical results and variation of measured ionized calcium concentration (miCa).AnimalsA t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
66
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(72 citation statements)
references
References 38 publications
5
66
1
Order By: Relevance
“…MARS model statistics were performed by the software of the public domain R version 3.4.2 (R project, Vienna, Austria). A MARS model was used to create the predictive algorithm in the same way as it was done in dogs . Briefly, a MARS model is a nonparametric regression technique that approximates complex non‐linear relationships by a series of hinge functions of the predictors expressed by the formula: italicpiCa=a0+k=1pak*hk()x, where a 0 is the intercept of the model, p is the total number of hinge functions, a k is the coefficient of the k th hinge function h k (x) , and x is a predictor.…”
Section: Methodsmentioning
confidence: 99%
“…MARS model statistics were performed by the software of the public domain R version 3.4.2 (R project, Vienna, Austria). A MARS model was used to create the predictive algorithm in the same way as it was done in dogs . Briefly, a MARS model is a nonparametric regression technique that approximates complex non‐linear relationships by a series of hinge functions of the predictors expressed by the formula: italicpiCa=a0+k=1pak*hk()x, where a 0 is the intercept of the model, p is the total number of hinge functions, a k is the coefficient of the k th hinge function h k (x) , and x is a predictor.…”
Section: Methodsmentioning
confidence: 99%
“…A recent study developed a model for predicting iCa status in dogs based on numerous results available on a biochemical profile in dogs . This model had high PPV (90%) and specificity (99.6%), and moderate sensitivity (64%).…”
Section: Discussionmentioning
confidence: 99%
“…Ionized calcium measurements were performed using an ion‐selective electrode analyzer. The other inclusion criteria were: (1) availability of a measured ionized calcium (miCa) reference interval (RI) specific to each analyzer, and (2) the use of biochemistry analyzers that were different from the Roche Hitachi 917 (Roche Diagnostics, Indianapolis, Indiana) and Olympus AU680 (Beckman Coulter, Inc, Brea, California), which were previously used for development and internal validation of the predictive model . Measured iCa RIs must have been determined using more than 20 healthy dogs and should have been specific to the sampling methods used; otherwise, transference of the RIs must have been verified for each sampling method using 20 healthy dogs .…”
Section: Methodsmentioning
confidence: 99%
“…However, previous studies have demonstrated that tCa might not adequately reflect the ionized calcium status of dogs . There have been several attempts to create formulas to correct tCa and improve the prediction of ionized calcium . However, the older formulas are not currently recommended.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation